Analysis of the type specimens of Fragilaria alpestris (Bacillariophyta) with description of two new ‘araphid’ species from the sub-Antarctic and Arctic Region - van De Vijver, Bart; Tusset, Eduardo; Williams, David M.; Ector, Luc (Phytotaxa, 2020)
During a survey of the sub-Antarctic diatom flora, several populations previously identified as Fragilaria alpestris were reanalysed and compared with type material of the latter species. The morphological ultrastructure of the type of F. alpestris, the sub-Antarctic populations and an additional population of F. cf. alpestris from Spitsbergen has been analysed using light and scanning electron microscopy observations. The analysis revealed that Fragilaria alpestris clearly belongs to the genus Fragilaria whereas the sub-Antarctic populations show all morphological features of the genus Staurosira. Comparison with similar taxa worldwide showed that these populations belonged to an unknown taxon that could not be identified using the currently available literature. A new species, Staurosira vandenbusscheana Van de Vijver sp. nov. is therefore described. The F. cf. alpestris population from Spitsbergen forms long, ribbon-like colonies, unlike the type of F. alpestris that never produces band-like colonies. Following the observation of additional morphological differences such as the presence of two rimoportulae and the shape of the linking spines, the Spitsbergen taxon is described as a new species: Fragilaria confusa sp. nov. The three taxa described herein share a number of morphological features. Their specific features are detailed below along with notes on their ecology. A literature survey and an analysis of the records for F. alpestris are given.